Advancements and prospects of CRISPR/Cas9 technologies for abiotic and biotic stresses in sugar beet - Misra, Varucha; Mall, A. K.; Pandey, Himanshu; Srivastava, Santeshwari; Sharma, Avinash (Frontiers in Genetics, 2023)
Sugar beet is a crop with high sucrose content, known for sugar production and recently being considered as an emerging raw material for bioethanol production. This crop is also utilized as cattle feed, mainly when animal green fodder is scarce. Bioethanol and hydrogen gas production from this crop is an essential source of clean energy. Environmental stresses (abiotic/ biotic) severely affect the productivity of this crop. Over the past few decades, the molecular mechanisms of biotic and abiotic stress responses in sugar beet have been investigated using next generation sequencing, gene editing/silencing, and over-expression approaches. This information can be efficiently utilized through CRISPR/Cas technology to mitigate the effects of abiotic and biotic stresses in sugar beet cultivation. This review highlights the potential use of CRISPR/Cas technology for abiotic and biotic stress management in sugar beet. Beet genes known to be involved in response to alkaline, cold, and heavy metal stresses can be precisely modified via CRISPR/Cas technology for enhancing sugar beet's resilience to abiotic stresses with minimal off-target effects. Similarly, CRISPR/Cas technology can help generate insect-resistant sugar beet varieties by targeting susceptibility-related genes, whereas incorporating Cry1Ab and Cry1C genes may provide defense against lepidopteron insects. Overall, CRISPR/Cas9 technology may help enhance sugar beet's adaptability to challenging environments, ensuring sustainable, high-yield production.